Effect of COVID-19 pandemic in Oral and Maxillofacial Surgery and Traumatology: the comparative study (Research, Society and Development, 2021)
The COVID-19 pandemic promoted the commitment of the health system in many countries. This study retrospective was realized to evaluate the effect promoted for the pandemic in Oral and Maxillofacial Surgery and Traumatology Service at Hospital Universitario do Oeste do Paraná, in Cascavel. A sample with patients in the pandemic period, between March 16th, 2020, and March 15th, 2021, as compared with patients in the previous year, called pre-pandemic. The data was categorized by the total of patients, admission date and hourly, and etiology. Age variations and gender were evaluated also. Statistics were admitted with significance at p